A possible role for CD26/DPPIV enzyme activity in the regulation of psoriatic pruritus. Issue 3 (June 2017) - Komiya, Eriko; Hatano, Ryo; Otsuka, Haruna; Itoh, Takumi; Yamazaki, Hiroto; Yamada, Taketo; Dang, Nam H.; Tominaga, Mitsutoshi; Suga, Yasushi; Kimura, Utako; Takamori, Kenji; Morimoto, Chikao; et al.
Highlights: Serum levels of sCD26 and sDPPIV enzyme are increased in patients with PSO. Truncated form of SP cleaved by DPPIV enzyme is increased in sera of PSO patients. DPPIV inhibitor suppresses IMQ-induced psoriatic itch and SP-induced pruritus. Overexpression of CD26/DPPIV exaggerates IMQ-induced psoriatic itch. Abstract: Background: Psoriasis (PSO) is one of the most common chronic inflammatory skin diseases, and pruritus affects approximately 60–90% of patients with PSO. However, the pathogenesis of pruritus in PSO remains unclear. Dipeptidyl peptidase IV (DPPIV) enzyme activity is involved in the regulation of peptide hormones, chemokines and neurotransmitters. Objectives: Our aim is to evaluate for a potential association between DPPIV and an increased risk of pruritus, and to identify possible underlying treatment targets in affected patients. Methods: Utilizing clinical serum samples of PSO patients and in vivo experimental pruritus models, we evaluated for a potential association between DPPIV and an increased risk for pruritus, and attempted to identify possible underlying treatment targets in pruritus of PSO. Results: We first showed that levels of DPPIV enzyme activity in sera of patients with PSO were significantly increased compared to those of healthy controls. We next evaluated levels of substance-P (SP), which is a neurotransmitter for pruritus and a substrate for DPPIV enzyme. Truncated form SP cleaved by DPPIV was significantly increased in sera of PSO. In an in vivo pruritus model induced by SP, scratching was decreased by treatment with a DPPIV inhibitor. Moreover, DPPIV-knockout mice showed attenuation of scratching induced by SP. Finally, scratching was decreased following the administration of a DPPIV inhibitor in an imiquimod-induced PSO model. On the other hand, scratching induced by imiquimod was increased in DPPIV overexpressing-mice. Conclusions: These results suggest that inhibition of DPPIV enzyme activity regulates pruritus in PSO.